Nullity and conformation of business contracts by authorities - Fauceglia, Domenico (CUADERNOS DE DERECHO TRANSNACIONAL, 2018)
Since the inclusion in the Italian institutional system of the c.d. Independent authori-ties, which are given the power to regulate sensitive sectors of the market (domain sensibles), attention has been focused on the particular interference between market regulation and contract discipline. In particular, the Authorities have quite a varied regulatory power: the law gives the Authorities the power to define the starting and conclusion procedures, as well as the form and minimum content of the contracts. In relation to these last powers, we will try, with this contribution, to examine the hy-pothesis of negotiation nullity deriving from the non-conformity of the contracts with the regulations of the Independent Authorities, as well as the hypothesis of external regulation of the contracts by the regulations of Independent Authorities.